Biological availability of phosphorus from natural phosphates for bovines by the isotope dilution technique - Lopes, Henrique Otávio da Silva; Vitti, Dorinha Miriam Silber Schmidt; Pereira, Eurípedes Alves; Abdala, Adibe Luiz; Moraes, Elino Alves de; Filho, José Cleto da Silva; Fichtner, Suzete Silveira (Pesquisa Agropecuaria Brasileira, 2014)
A metabolism trial was carried out with steers to study the true absorption of phosphorus from dicalcium phosphate and Brazilian rock phosphates from Patos and Tapira. Twenty-seven steers were assigned to three treatment groups in a randomized block design: dicalcium phosphate (DICAL) and natural rock phosphate from Patos de Minas (FP) and Tapira (FT). The animals were confined in metabolic cages and received a basal ration of Brachiaria decumbens hay and a concentrate with the appropiate phosphorus source. The endogenous fecal loss of phosphorus was estimated by the isotope dilution method using 32P as a tracer. The true absorption of phosphorus was 65,88±8,46; 46,21±7,15 and 44,43±9,67% for DICAL, FP and FT, respectively. True phosphorus absorption was higher (P < 0,01) for the streers receiving DICAL than for those fed FP and FT.